Creating interactive names for national parks in Indonesia using smart apps creator on android - Haida Dafitri; Ilham Maulana; Efendi Napitupulu; Agus Junaidi (Jurnal Mantik, 2023)
Indonesia faces a crisis in education due to limited knowledge about national identity, potentially leading to a crisis in the future. To address this, an interactive game using Android technology has been developed to help students understand national identity. The Multimedia Development Life Cycle (MDLC) and Smart Apps Creator technology are used in game development. The goal is to create interactive educational games to inform society about Indonesia and promote nationalism.